Determination of biodiesel blending percentages using natural abundance radiocarbon analysis: Testing the accuracy of retail biodiesel blends - Reddy, C. M.; DeMello, J. A.; Carmichael, C. A.; Peacock, E. E.; Xu, L.; Arey, J. S. (Environmental Science & Technology, 2008)
Blends of biodiesel and petrodiesel are being used increasingly worldwide. Due to several factors, inaccurate blending of these two mixtures can occur. To test the accuracy of biodiesel blending, we developed and validated a radiocarbon-based method and then analyzed a variety of retail biodiesel blends. Error propagation analysis demonstrated that this method calculates absolute blend content with +/- 1% accuracy, even when real-world variability in the component biodiesel and petrodiesel sources is taken into account. We independently confirmed this accuracy using known endmembers and prepared mixtures. This is the only published method that directly quantifies the carbon of recent biological origin in biodiesel blends. Consequently, it robustly handles realistic chemical variability in biological source materials and provides unequivocal apportionment of renewable versus nonrenewable carbon in a sample fuel blend. Analysis of retail biodiesel blends acquired in 2006 in the United States revealed that inaccurate blending happens frequently. Only one out of ten retail samples passed the specifications that the United States Department of Defense requires for blends that are 20% biodiesel (v/v; referred to as B20).
id: 1864; 281JN Times Cited:3 Cited References Count:39; YY